In vitro and In vivo evaluation of resin composites fluorescence - Lopes, Gabriéla Melo; Prado, Taiana Paola [UNESP]; Camilotti, Veridiana; Bernardon, Paula; Mendonça, Marcio José; Ueda, Julio Katuhide (Elsevier, 2021)
This study aimed at comparatively evaluate, by visual method, the fluorescence intensity in vitro and in vivo of six resins composed of different classifications and viscosities compared to natural enamel. For the in vitro study, seventy specimens were prepared and for the in vivo study, a restoration was performed on the cervical portion of the buccal face of 6 anterior maxillary teeth, which under ultraviolet light were compared to the dental structure. The specimens and restorations were photographed only under the illumination of an ultraviolet lamp. The photographic record was performed, with standardized parameters for all photographs (ISO 100). After visual analysis of the images by three evaluators calibrated in the in vitro study and by ten evaluators calibrated in the in vivo study, numerical values were assigned to resins without fluorescence (zero), medium fluorescence (1) and high fluorescence (2). The evaluations were submitted to the Kruskal-Wallis and Dunn test, which among the limitations of this study and according to the employed methodology, it was found that there was no statistical difference in fluorescence intensity among the composite resins evaluated, since all types of resins achieved fluorescent metamerism with dental enamel.
Keywords: Composite resin; Flow resin; Fluorescence; Optical properties